FMECA Application to Intraoperative Electron Beam Radiotherapy Procedure As a Quality Method to Prevent and Reduce Patient’s Risk in Conservative Surgery for Breast Cancer - Vidali, Cristiana; Severgnini, Mara; Urbani, Monica; Toscano, Licia; Perulli, Alfredo; Bortul, Marina (Frontiers in Medicine, 2017)
Introduction. Failure Mode Effects and Criticalities Analysis (FMECA) represents a prospective method for risk assessment in complex medical practices. Our objective was to describe the application of FMECA approach to intraoperative electron beam radiotherapy (IOERT), delivered using a mobile Linear Accelerator, for the treatment of early-breast cancer as an anticipated boost. Material and Methods . A multidisciplinary Working Group, including several different professional profiles, was created before the beginning of clinical practice in 2012, with the purpose of writing the Flow Chart and applying the FMECA methodology to IOERT procedure. Several criticalities were identified a priori in the different steps of the procedure and a list of all potential failure modes (FM) was drafted and ranked using the risk priority number (RPN) scoring system, based on the product of three parameters: severity, occurrence and detectability (score between 1 and 5). The actions aimed at reducing the risk were then defined by the Working Group and the risk analysis was repeated in 2014 and in 2016, in order to assess the improvement achieved. Results. Fifty-one failure modes were identified, which represented the issues prospectively investigated according to the FMECA methodology. Considering a set threshold of 30, the evaluated RPNs show that 33 out of 51 failure modes are critical; 6 are included in the moderate risk class (RPN: 31-40); 16 in the intermediate risk class (RPN: 41-50) and 11 in the high risk class (RPN: > 50). Discussion. The most critical steps concerned the surgical procedure and IOERT set-up. The introduction of the corrective actions into the clinical practice achieved the reduction of the RPNs in the re-analysis of the FMECA worksheet after two and four years, respectively. Conclusions. FMECA proved to be a useful tool for prospective evaluation of potential failures in IOERT and contributed to optimize patient safety and to improve risk management culture among all the professionals of the Working Group.